Marketing Strategy for Creative SMEs in Entering the Export Market - Elsya Rima Dalia Muhlas; Suci Prihatiningtyas; Mar'atul Fahimah (LPPM Universitas KH. A. Wahab Hasbullah, 2021)
This study aims to determine the target market carried out by AMMIC (Association of Independent IKM Creative Partners) in order to support the export activities of SME/IKM products. AMMIC (Association of Mandiri IKM Creative Partners) is an organization that exports and markets hardcraft and Food and Beverage products. The method used is a case study, which takes a certain object for in-depth analysis to provide the results of an analysis of the export-scale SME market development at AMMIC (Association of Independent IKM Creative Partners) with data collection techniques, namely interviews, literature studies, and observations and it can be concluded that the target export-scale SME market using product strategy, price strategy, distribution strategy, promotion strategy. Some of the obstacles faced when the products are to be exported, one of which is the limited cost for exports which is quite large. Food, beverage and craft SMEs must pay for official barcode registration, packaging design fees, registration of Haki (Industrial Brands and Designs), Halal Certification, distribution permits and other costs, including promotional costs in order to compete in the export market. This considerable cost can be borne together in an AMMIC group that builds common strength which is based on the spirit of living together.